The Influence of Financial Literacy on Financial Resilience through Financial Planning (Study on BUMDes in East Java) - Ida Ayu Sri Brahmayanti; Gustaf Naufan Febrianto (Universitas Dr. Soetomo, 2024)
This research aims to investigate the influence of financial literacy on financial resilience through financial planning, with a special focus on Village-Owned Enterprises (BUMDes) in East Java. Quantitative research methods were used with stratified random sampling techniques to select representative BUMDes samples. The research instrument is a structured questionnaire that measures the level of financial literacy, financial planning and financial resilience of BUMDes. The results of data analysis using the Structural Equation Modeling-Partial Least Square (SEM-PLS) approach show that there is a significant positive relationship between the level of financial literacy and financial planning on the financial resilience of BUMDes. The implications of this research provide an in-depth understanding of the importance of financial literacy and financial planning in increasing the financial resilience of BUMDes, so that it can help in designing more effective policies and training programs to support local economic growth at the village level.